Enter Yossarian: How to Resolve the Procedural Catch-22 That the Private Securities Litigation Reform Act Creates - Elliott J. Weiss; Janet E. Moser (Washington University Law Quarterly, 1998)
Section II of this Article sets forth our understanding of what the Reform Act requires a plaintiff to set forth in a complaint to state a valid claim that a corporation has made false or misleading public statements in violation of section 10(b) and Rule 10(b)(5). Section III describes our case study of GTF. Section IV analyzes the options a court would face in a case similar to the "quasi-hypothetical" we studied and suggests the option we believe a court should choose.
Keywords: Pleading; Discovery (Law); Securities fraud; Private Securities Litigation Reform Act of 1995; Class actions (Civil procedure)